Food and agriculture in Ethiopia: Progress and policy challenges - Dorosh, Paul A.; Rashid, Shahidur (International Food Policy Research Institute, 2013)
Ethiopia has made considerable progress toward food security since the 1984 famine captured worldwide media attention. Almost 30 years after that calamity, Ethiopian per capita income has increased, poverty has fallen, food security has improved, and the groundwork has been laid for sustained economic growth.